2019
DOI: 10.1016/j.cell.2019.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-cellular Rewiring of the Human Colon during Ulcerative Colitis

Abstract: Highlights d 51 cell subsets in colon mucosa of 18 ulcerative colitis and 12 healthy individuals d M-like cells, inflammatory monocytes and fibroblasts, and CD8 + IL-17 + T cells expand in disease d Oncostatin M circuit in inflammatory monocytes and fibroblasts may affect drug response d Co-expression of genes within cells allows inference of causal genes across risk loci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

86
1,373
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,004 publications
(1,469 citation statements)
references
References 77 publications
86
1,373
10
Order By: Relevance
“…Of interest, LEFTY1 is a developmental gene, the role of which in adult tissue remains to be investigated. Recently, LEFTY1 has been identified as a marker of colonic stem cells both in fetal and adult large intestine . This is consistent with the LEFTY1 staining we observed in the normal colon.…”
Section: Discussionsupporting
confidence: 91%
“…Of interest, LEFTY1 is a developmental gene, the role of which in adult tissue remains to be investigated. Recently, LEFTY1 has been identified as a marker of colonic stem cells both in fetal and adult large intestine . This is consistent with the LEFTY1 staining we observed in the normal colon.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of IL11 on the vasculature will be discussed elsewhere. Considered together with patient studies that show IL11 to be highly upregulated in the colonic mucosa of patients with ulcerative colitis or Crohn's disease [24][25][26], our results highlight IL11 as a promising therapeutic target for IBD, particularly in the context of anti-TNF therapy resistance.…”
Section: Discussionmentioning
confidence: 54%
“…In humans, IL11 is highly upregulated in the colonic mucosa of patients with either ulcerative colitis or Crohn's disease who do not respond to anti-TNF therapy, with recent single cell RNA-seq studies localizing IL11 to inflammatory mucosal stromal cells [24][25][26]. To better understand the effect of IL11 in the colon, recombinant human IL11 has been used in rodent models of IBD [27][28][29][30] and it was suggested that IL11 may have a protective role in the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…While fibroblasts have been implicated in inflammation-associated pathology of rheumatoid arthritis, colitis and IPF (7,(15)(16)(17)(18), it has not been shown conclusively whether the stroma is a modifier or primary driver of the inflammatory response. In the BLM model of lung fibrosis, we found that the deletion of IL11 signaling in fibroblasts alone is sufficient to protect mice from inflammation in the lung.…”
Section: Combined Results and Discussionmentioning
confidence: 99%
“…Further studies are required to delineate whether distinct subpopulations of IL11-responsive fibroblasts drive lung fibrosis and inflammation. It will also be important to examine whether IL11-dependent, fibroblast-mediated inflammation occurs in other lung diseases, such as asthma (26,27) or additional conditions such as rheumatoid arthritis or colitis (15)(16)(17)(18). Preliminary functional studies suggest this may be the case, at least for colitis (10), which is characterized by IL11expressing inflammatory fibroblasts that predict disease severity in patients (17).…”
Section: Combined Results and Discussionmentioning
confidence: 99%